2013
DOI: 10.1002/2013jd020507
|View full text |Cite
|
Sign up to set email alerts
|

Trends in aerosol optical depth over Indian region: Potential causes and impact indicators

Abstract: [1] The first regional synthesis of long-term (back to~25 years at some stations) primary data (from direct measurement) on aerosol optical depth from the ARFINET (network of aerosol observatories established under the Aerosol Radiative Forcing over India (ARFI) project of Indian Space Research Organization over Indian subcontinent) have revealed a statistically significant increasing trend with a significant seasonal variability. Examining the current values of turbidity coefficients with those reported~50 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
141
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 234 publications
(157 citation statements)
references
References 58 publications
14
141
0
Order By: Relevance
“…Recently, Babu et al have discussed long-term regional AOD trends over the Indian region using the database from the network of observatories equipped with MWR instruments. More details about this system, its data deduction methodology, error budgeting, and comparison of its performance with other instruments are extensively available in the literature 23,24,32 .…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Babu et al have discussed long-term regional AOD trends over the Indian region using the database from the network of observatories equipped with MWR instruments. More details about this system, its data deduction methodology, error budgeting, and comparison of its performance with other instruments are extensively available in the literature 23,24,32 .…”
Section: Datamentioning
confidence: 99%
“…This observatory is also a part of the network of observatories under Aerosol Radiative Forcing over India (ARFI) project of ISRO-GBP, which is now known as ARFINET 23,24 . Some of the findings from this observatory have been published earlier [25][26][27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…These stations are part of the ARFINET chain 28 . For BC, the continuous measurements have been carried out using inter-compared Aethalometers (Magee Scientific Ins, USA) following a common measurement protocol at the chosen location.…”
Section: Observational Datamentioning
confidence: 99%
“…These stations formed the components of the ARFINET chain 28 . At these stations, BC mass concentrations have been measured using inter-compared Aethalometers, following a common measurement protocol.…”
Section: Ground-based Measurements (Arfinet)mentioning
confidence: 99%
“…There is an increasing trend of aerosols over the Indo-Gangetic Plain (IGP) region during pre-monsoon and summer monsoon seasons which is mainly attributed to the combined effects of dust transport and wet deposition of aerosol [4] . Many studies [5][6][7][8] have revealed the aerosol environment over Dibrugarh, a remote continental location in North-East India on the basis of ground based observations.…”
Section: Introductionmentioning
confidence: 99%